4, 4'Dimethoxychalcone: a natural flavonoid that promotes health through autophagy-dependent and -independent effects. Issue 9 (2nd September 2019) - Zimmermann, Andreas; Kainz, Katharina; Hofer, Sebastian J.; Bauer, Maria A.; Schroeder, Sabrina; Dengjel, Jörn; Pietrocola, Federico; Kepp, Oliver; Ruckenstuhl, Christoph; Eisenberg, Tobias; Sigrist, Stephan J.; Madeo, Frank; et al.
ABSTRACT: The age-induced deterioration of the organism results in detrimental and ultimately lethal pathologies. The process of aging itself involves a plethora of different mechanisms that should be subverted concurrently to delay and/or prevent age-related maladies. We have identified a natural compound, 4, 4ʹ-dimethoxychalcone (DMC), which promotes longevity in yeast, worms and flies, and protects mice from heart injury and liver toxicity. Interestingly, both the DMC-mediated lifespan extension and the cardioprotection depend on macroautophagy/autophagy whereas hepatoprotection does not. DMC induces autophagy by inhibiting specific GATA transcription factors (TFs), independently of the TORC1 kinase pathway. The autophagy-independent beneficial effects of DMC might involve its antioxidative properties. DMC treatment results in a phylogenetically conserved, systemic impact on the metabolome, which is most prominently characterized by changes in cellular amino acid composition. Altogether, DMC exerts multiple, geroprotective effects by igniting distinct pathways, and thus represents a potential pharmacological agent that delays aging through multipronged effects.